Nanoliposome-sericin hydrogel microneedle patches effectively alleviate inflammation and scavenge ROS for the treatment of CKD-aP - Lichang Liu; Longbao Feng; Yuanyuan Zhang; Junjie Xu; Le Liu; Lichun Wang; Weihong Hong; Yuyan Jin; Jiahao Zeng; Peihua He; Xusheng Liu (Materials Today Bio)
Chronic Kidney Disease-associated Pruritus (CKD-aP) is a debilitating condition commonly observed in patients with chronic kidney disease (CKD), characterized by severe skin itching and inflammation. Despite the availability of oral medications and topical treatments, their efficacy is limited, and systemic side effects are a significant concern. This study presents the development of a novel microneedle system (Cap@Lip/Dife-MNs), designed to address CKD-aP through targeted and sustained drug delivery. The system integrates liposome-encapsulated capsaicin, known for its anti-inflammatory and analgesic effects, with methacryloyl sericin (SerMA) hydrogel-loaded Difelikefalin, a drug that modulates neural transmission and immune responses. Liposomes enhance the solubility and stability of capsaicin, while the SerMA hydrogel provides sustained release of Difelikefalin. The Cap@Lip/Dife-MNs system demonstrates excellent drug delivery capabilities, promoting skin cell proliferation, reducing oxidative stress, and alleviating pruritus by modulating neural signaling pathways. In vivo transcriptomic analysis revealed significant modulation of immune-related genes and reduction of oxidative stress markers, confirming its immune-regulatory and anti-inflammatory effects. Moreover, neural signal analysis showed reduced pruritus-related transmission, emphasizing its potential as a non-invasive, effective treatment for CKD-aP. These findings highlight the Cap@Lip/Dife-MNs microneedle system as a promising therapeutic platform for CKD-aP, with strong potential for clinical application.